A Multidisciplinary Approach to Health and Safety Leadership in New Zealand: An "All of Person" Approach: Embracing Whanaungatanga and Manaakitanga: A Multidisciplinary Approach to Health and Safety Leadership in New Zealand - Knobel, Nicola (New Zealand Journal of Health and Safety Practice, 2024)
This article explores a comprehensive approach to Workplace Health and Safety (WHS) leadership in New Zealand. It delves into the integration of inclusivity, vulnerability, Safety II principles, and Te Ao Māori values into WHS practices. The holistic vision presented emphasises proactive leadership, education, and cultural responsiveness to create a paradigm shift in WHS. By prioritising well-being and inclusivity, this approach aims to transcend compliance-driven WHS models, fostering a culture where safety is everyone's responsibility. The article calls for action, inviting organisations to embrace this transformative leadership model for a safer, more empathetic future in New Zealand workplaces. Workplace Health and Safety, Leadership, Holistic Approach, New Zealand, Te Ao Māori